Recurrent Urinary Tract Infection- Etiology, Risk Factors and Outcome in a Tertiary Care Hospital of Bangladesh - Mahmood, Nazneen; Siddiqui , Mahmudur Rahman; Giasuddin , Rubayat Sheik; Islam, Maria; Siddiqui, Md Niamul Kabir Khan (Bangladesh Journal of Medicine, 2024)
Background: Urinary tract infections (UTIs) are one of the major causes of morbidity and comorbidities in patients with underlying conditions, and it accounts for the majority of the reasons for hospital visit globally. The high prevalence of recurrent UTIs represents a modifiable determinant for both societal and personal burdens, hence the importance of disease prophylaxis. Consultations for UTIs represent between 1% and 6% of all medical visits ( 7 million visits and US1.6 billion annually). They are associated with a significant burden of morbidity and mortality in the elderly, among whom UTIs are most prevalent. Methods: This cross-sectional descriptive type of observational study was conducted in the Department of Nephrology in Anwer Khan Modern Medical College Hospital, Dhaka, Bangladesh from January 2023, to December 2023. A total no of 93 patients were included in the study. Inpatients, age range 21-85 years, presenting or highly suspicious of having UTIs and the occurrence of ≥2 symptomatic episodes within 6 months or ≥3symptomatic episodes within 12 months were recruited in the study. Any patient who was terminally ill, who fails to give urine samples, with a history of antibiotic administration in the last two weeks and any female who was in their menstruation period were excluded from the study. Results: Among them 79 were female and 14 were male. Female to male ratio was 5.64:1. Mean age of the patients was 58.61±17.51 (Mean±SD). Most of the patients were of 61-70 years age group 23/93 (24.73%) and after that41-50 years 19/93 (20.43%). 92.47% (86/93) were married and 7.53% (7/93) were unmarried. Most of the patients were of Diabetes mellitus (DM) 57/93 (61.29%). After that Hypertension, Chronic Kidney Disease (CKD) and CKD + DM about 51/93 (54.84%), 39/93 (41.94%) and 36/93 (38.71%) respectively. 54/79 (68.35%) were of menopause and 24/79 (30.38%) women had regular menstrual cycle. 1/79 (1.27%) was pregnant.Escherichia coli(E coli) was the most prevalent uropathogens with 47/93 (50.54%) followed by Klebsiella pneumoniae 12/93 (12.90%), Pseudomonas aeruginosa 10/93 (10.75%), Streptococcus pyogenes 8/93 (8.60%), Staphylococcus aureus 6/43 (6.45%), Enterococcus faecalis 5/93 (5.38%) and others 5/93 (5.38%). 77.42% were of relapse and 22.52% were of reinfection. The Mean±SD of HbA1c was 7.83±2.15% and that of Serum creatinine and Hemoglobin were 2.17±1.18 mg/dl and 9.82±2.60gm%. On routine examination of urine, 39/93 (41.94%) patient had trace albumin present in urine and 57/93 (61.29%) had reducing sugar. 71/93 (76.34%) had1-2 pus cell in urine and 22/93 (23.66%) presented with plenty of pus cell with 19/93 (20.43%) had 0-4 RBC’s (Red blood cell). Factors associated with recurrent UTI were Age >50 years (56.99%), Female gender (84.95%), Married (92.47%), Menopause (58.06%), Diabetes mellitus (61.29%), Indwelling catheter >6 days (25.81%) and Genitourinary abnormalities (15.05%). Conclusion: This study has demonstrated that hospitalization, married individuals, duration of catheter, diabetes mellitus, genitourinary tract abnormalities, female gender and menopause are the most important factors associated with UTIs. Appropriate measures may help to reduce UTIs due to these associated factors. We recommend routine UTIs screening of patients of the following category: hospitalized, genitourinary tract abnormalities, indwelling catheter, diabetic, female gender, menopause and married individuals. If these routine checks are put in place, prevention of UTI can be realized at lower cost. Bangladesh J Medicine 2024; 35: 173-179